Effect of Efavirenz on Endogenous Progesterone Concentrations and Contraceptive Outcomes among Ugandan HIV Infected Women Coadministering Ethinylestradiol/Levonorgestrel - Grant Munkwase; Kuteesa R. Bisaso; Othman Kakaire; Sarah Nanzigu (AIDS Research and Treatment)
This study assessed the effect of efavirenz mid-dose plasma concentrations on mid-luteal endogenous progesterone concentrations and contraceptive outcomes among 49 HIV infected women coadministering ethinylestradiol/levonorgestrel, including 34 HIV positive women on Highly Active Antiretroviral Therapy (HAART) and 15 HAART naïve HIV infected women, purposively selected from Mulago Hospital, Uganda. A blood sample was collected once between days 20 and 22 of each woman’s menstrual cycle for measuring endogenous progesterone and efavirenz concentrations by electrochemiluminescence technology and High Performance Liquid Chromatography (HPLC), respectively. Descriptive statistical analysis and correlation and logistic regression analysis were done using SPSS v.21 and R3.1. Efavirenz showed a weak positive linear relationship with endogenous progesterone at efavirenz concentrations below 12 μg/ml. Based on serum endogenous progesterone, the observed hormonal contraceptives failure rate (24.5%) was higher than expected (maximum 8%). A higher proportion of HIV positive women on efavirenz based HAART (26.5%) was at risk of contraceptive failure than their HIV infected HAART naïve counterparts (20%) though it was not statistically significant (p=0.63). Efavirenz mid-dose plasma concentrations seem to have no significant effect on mid-luteal endogenous progesterone concentrations and contraceptive outcomes among HIV infected Ugandan women coadministering ethinylestradiol/levonorgestrel oral pills.